Variasi Tutur Pada “Santi” Ditinjau dari Pandangan Neurolinguistik - Johan, Mhd; Rudianto, Gaguk; Satria, Robby (eScience Humanity Journal, 2025)
The purpose of this study is to identify speech variations that occur in respondents in the utterances uttered by respondents when producing words. In analyzing this data, the researcher uses a theoretical basis. These theories come from Sastra, Johan, Caplan. In addition, the author searches for data and the method used to obtain data is the listening and engaging conversation method initiated by Sudaryanto and Nadra, the way this method works is that researchers are directly involved in obtaining data by encouraging respondents to talk. After the data is obtained, the researcher begins to analyze it using the distribution method and uses the direct element sharing technique. After analyzing all the data, the researcher gets the results, the results obtained are the occurrence of two events, the event is a loss event, in the loss event, three loss events occur, the events are the front loss event, the middle loss event and the back loss event. Then the occurrence of a change event. In these events, there is a change in the meaning of the word and some have no meaning.